JAVANESE SPEAKING SKILL OF PRIVATE UNIVERSITY STUDENTS IN CENTRAL JAVA - Nurpeni Priyatiningsih, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Evaluation of oral expression (micara) course shows that students speaking Javanese are frequently influenced by Indonesian. The use of improper ‘unggah-ungguh’ (speech level) from grammatical variety of ‘krama inggil’ (high speech level) is also often found. A positive attitude on Javanese is required in order to succeed in mastering Javanese speaking skill. Another supporting aspect in speaking activities is the logical thinking ability. The speaker should be able to identify messages, ideas, and thoughts, and then deliver them properly and coherently, in a well-organized way. The objectives of this research are to find the strength of the correlation of the students' logical thinking ability, Javanese speech level mastery, and attitude on Javanese language to Javanese speaking skill both individually and collectively. It was carried out at several Javanese language and literature education departments of private universities in Central Java namely: PBSJ-FKIP Bantara Veteran University of Sukoharjo, Muhammadiyah University of Purworejo, and PGRI Institute of Teacher Training and Education of Semarang. The samples of the research were 90 students and were taken by using the purposive random sampling technique. The data of research were analyzed by using the correlational model of analysis. The results of research show that: (1) there is a positive correlation between the students’ logical thinking ability and their Javanese speaking skill; (2) there is a positive correlation between the students’ Javanese speech level mastery and their Javanese speaking skill; (3) there is a correlation between the students' attitude on Javanese language and their Javanese speaking skill; and (4) there is a simultaneously significant correlation of the students’ logical thinking ability, speech level mastery, and attitude on their Javanese language altogether to Javanese speaking skill. Thus, the proposed hypotheses are verified.